2008
DOI: 10.1159/000185524
|View full text |Cite
|
Sign up to set email alerts
|

An Incoherent Magnetic Field Inhibited EGF Receptor Clustering and Phosphorylation Induced by a 50-Hz Magnetic Field in Cultured FL Cells

Abstract: Previously, we found that exposure to a 50-Hz magnetic field (MF) at 0.4 mT could induce epidermal growth factor (EGF) receptor clustering in Chinese hamster lung (CHL) fibroblast cells and superposition of an incoherent MF with the same intensity could inhibit the effect. In the present experiment, we investigated the effects of 50-Hz MF exposure at different intensities on EGF receptor clustering and phosphorylation in human amniotic cells (FL), and explored the interaction effect of an incoherent MF. Cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 34 publications
2
24
0
Order By: Relevance
“…When the incoherent MF was superimposed, the inhibitory effects on hormone secretion induced by the 50-Hz MF were eliminated. Our previous studies also found that superposition of an incoherent MF with the same intensity could inhibit 50-Hz MF-induced gap junction intercellular communication suppression [38], EGF receptor clustering and phosphorylation [18], and Ras protein activation [39]. The present result further confirmed the hypothesis with a different cell model and biological endpoint.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…When the incoherent MF was superimposed, the inhibitory effects on hormone secretion induced by the 50-Hz MF were eliminated. Our previous studies also found that superposition of an incoherent MF with the same intensity could inhibit 50-Hz MF-induced gap junction intercellular communication suppression [38], EGF receptor clustering and phosphorylation [18], and Ras protein activation [39]. The present result further confirmed the hypothesis with a different cell model and biological endpoint.…”
Section: Discussionsupporting
confidence: 88%
“…The same MF exposure system used in our previous experiments [18] was used in this experiment. It consists of three groups of square copper coils (36×36 cm 2 ) placed inside an incubator (Model 3164, Forma, Marietta, GA, USA).…”
Section: Magnetic Field Exposure Systemmentioning
confidence: 99%
“…There, signal transduction pathways would be triggered through a complex program of transcriptional events involving activation of transcription factors. On the basis of these premises, the epidermal growth factor receptor (EGFR) has been proposed as one potential target of 50 Hz MF [42][43][44]. Also, activation of transcription factors associated to ERK activation has been described in human leukaemia cells HL-60, in human breast cancer cells MCF-7, and in rat fibroblast 3Y1, exposed to a 60 Hz, 100 µT MF [31].…”
Section: Discusionmentioning
confidence: 99%
“…SMFs have been shown to inhibit cancer cell proliferation in multiple studies, but the mechanism was unclear [17]. Cancer cells often proliferate in response to signaling from Receptor Tyrosine Kinases (RTKs), and the effect of magnetic fields on EGFR phosphorylation was the subject of several studies [810]. A 0.4 mT 50 Hz and a 2 μT 1.8GHz pulsed magnetic fields (electromagnetic waves frequency) both increased EGFR phosphorylation, which were reversed by incoherent (“noise”) magnetic fields of the same intensities [9, 10].…”
Section: Introductionmentioning
confidence: 99%